2002
DOI: 10.1097/00008469-200206000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Can physical trauma cause breast cancer?

Abstract: The objective of this study is to explore the effect of lifestyle on the risk of invasive breast carcinoma in women aged 50-65 years. A case-control study using a questionnaire and a semi-structured interview. Cases (n = 67) and controls (n = 134) were closely matched on known risk factors for breast cancer including age, family history, age at menarche, parity, age at first birth and menopausal status. Controls were chosen from a pool of 5600 women who attended for breast screening and filled in a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…Most studies [56–61], but not all [19, 62], show higher annual health care utilization among women with a history of abuse in childhood or adulthood relative to nonabused women. Finally, researchers have speculated that physical trauma to the breast can cause cancer [63, 64]. A case–control study of women aged 50–65 years found that women with breast cancer were more likely than controls to report physical trauma to the breast in the previous 5 years (OR = 3.3, 95% CI = 1.3–10.8) [64].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies [56–61], but not all [19, 62], show higher annual health care utilization among women with a history of abuse in childhood or adulthood relative to nonabused women. Finally, researchers have speculated that physical trauma to the breast can cause cancer [63, 64]. A case–control study of women aged 50–65 years found that women with breast cancer were more likely than controls to report physical trauma to the breast in the previous 5 years (OR = 3.3, 95% CI = 1.3–10.8) [64].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, researchers have speculated that physical trauma to the breast can cause cancer [63, 64]. A case–control study of women aged 50–65 years found that women with breast cancer were more likely than controls to report physical trauma to the breast in the previous 5 years (OR = 3.3, 95% CI = 1.3–10.8) [64]. According to models of epithelial cell generation, it is plausible that physical trauma could lead to cancer initiation [64, 65].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is not easy to answer this question, even using well-designed, populationbased samples 9 as retrospective evidence is difficult to acquire and may be unreliable because of recall bias in patients compared with controls. 10 It has been claimed that electricians have a higher risk of developing ALS compared with those in other occupations partly because of exposure to power frequency electromagnetic fields. [11][12][13] Before considering prospective studies of electrical injury as a possible trigger for neurodegenerative diseases including ALS, we decided to undertake a systematic review of all the existing literature, which extends back to 1906.…”
mentioning
confidence: 99%
“…This may constitute an indication for extraction of pellets in the breast tissue. This is further highlighted as models of epithelial cells generation indicate that a causal link exist between physical trauma and cancer [10]. This case presents a dilemma in decision and a subject of debate.…”
Section: Discussionmentioning
confidence: 94%